Making decent work a reality for domestic workers : progress and prospects ten years after the adoption of the Domestic Workers Convention, 2011 (No. 189). (International Labour Office, 2021)
"This report, published on the tenth anniversary of the ILO Domestic Workers Convention (No. 189), could not have come at a more critical time for domestic workers. The COVID-19 pandemic has underscored both the interdependence of domestic workers and the households they care for, and the vulnerability of the millions of domestic workers earning a living behind closed doors. The adoption of Convention No. 189 in 2011 represented an historic moment in the recognition of domestic work as real work. Ten years later, this report makes an unprecedented effort to measure if decent work has become a reality for domestic workers around the world. It highlights the progress made over a decade, but also the legal and implementation gaps that remain. Most importantly, it provides guidance on policies that can pave the way to make decent work a reality for domestic workers."--